Penerapan Fatwa DSN–MUI Nomor: 08/DSN–MUI/IV/2000 Dalam Praktik Akad Pembiayaan Musyarakah Di Perbankan Syariah (Studi Kasus Di PT. BPRS Tanmiya Artha Kediri) - Suprihantosa Sugiarto; Ali Samsuri; Retno Elok Catur Sari (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
This study aims to determine: 1) The practice of Musyarakah financing contracts at PT. BPRS Tanmiya Artha Kediri includes musharaka with syndication and 2) The practice of musyarakah financing contracts in the perspective of DSN-MUI Fatwa Number: 08/DSN-MUI/IV/2000 at PT. BPRS Tanmiya Artha Kediri, both general muyarakah and syndicated musyarakah. This research is a qualitative research with the type of case study. The results obtained are 1) The form of the Musyarakah financing contract is working capital on housing projects, electrical installations, agriculture, and car dealerships. Syndicated financing is carried out by inter-Islamic banks only, the average number is 2 to 5 banks that participate in financing in one syndication. The calculation of profit sharing is carried out using a revenue sharing system. The growth of musyarakah financing contracts rose very high at the end of 2019 due to syndicated financing between other Islamic banks. The first Musyarakah financing contract in 2019 was the result of a syndication with PT. A for housing project development, 2) Syndication of PT. A by using the musyarakah financing contract, he has complied with the rules contained in the DSN-MUI Fatwa, namely qabul consent, guarantees, capital, profits, dispute resolution, and a clear division of labor and is stated in writing in the agreement.